Gaya Kepemimpinan Kyai Pondok Pesantren Jannaturroichan Jombang dalam Membentuk Kemandirian Santri - Syahrul Udma; Chusnul Chotimah; Didin Sirojudin (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2024)
This research discusses the Kyai's leadership style in improving the quality of Islamic education by forming independent students. Like at the Jannaturroichan Islamic Boarding School, the santri at the Jannaturroichan Islamic Boarding School, in all aspects of needs within the scope of the Islamic Boarding School, are almost all run by the Santri independently. The author used descriptive qualitative research, by conducting observations, interviews and documentation at the Jannaturroichan Peterongan Islamic Boarding School, Jombang, so that the conclusion was that; The leadership style used by KH Yunus Roichan at the Jannaturroichan Islamic Boarding School is a paternalistic religious leadership style, he in the process of educating the students uses an interactive style between him and the students, and applies Islamic religious values by following the leadership style that has been exemplified by Prophet Muhammad SAW.